Peran Dukungan Sosial Keluarga dalam Membentuk Kematangan Karier Siswa SMP - Rahma, Ulifa; Rahayu, Esti Widya (Jurnal Ilmu Keluarga dan Konsumen, 2018)
The family is part of the process in forming student career maturity to be able to develop the career optimally. This study aimed to analyze the effect of the role of family social support on the career maturity of junior high school students and analyze the dimensions of family social support that play the most role. The participants of this study involved 133 junior high school students aged 12-15 years. The sampling technique used was simple random sampling. Data were collected through self-report and analyzed by simple linear regression analysis. The analysis showed that there was the role of family social support for the career maturity of junior high school students. Both variables had a positive relationship direction, which shows that the higher the family social support, the higher the career maturity of junior high school students; vice versa. The dimensions of family social support that play a role in the maturity of junior high school students’ career were social support and information. Family social support and career maturity of junior high school students in this study were in the high category. The highest family social support provided is appreciation support, then instrumental support, followed by information support and the lowest is emotional support.